TEMPO-Oxidized Cellulose Nanofiber-Alginate Hydrogel as a Bioink for Human Meniscus Tissue Engineering - Lan, Xiaoyi; Ma, Zhiyao; Szojka, Alexander R. A.; Kunze, Melanie; Mulet-Sierra, Aillette; Vyhlidal, Margaret J.; Boluk, Yaman; Adesida, Adetola B. (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: The avascular inner regions of the knee menisci cannot self-heal. As a prospective treatment, functional replacements can be generated by cell-based 3D bioprinting with an appropriate cell source and biomaterial. To that end, human meniscus fibrochondrocytes (hMFC) from surgical castoffs of partial meniscectomies, as well as cellulose nanofiber-alginate based hydrogels have emerged as a promising cell source and biomaterial combination. The objectives of the study were to first find the optimal formulations of TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl)-oxidized cellulose nanofiber/alginate (TCNF/ALG) precursors for bioprinting, and then to use them to investigate redifferentiation and synthesis of functional inner meniscus-like ECM components by expanded hMFCs. Methods: The rheological properties including shear viscosity, thixotropic behavior recovery, and loss tangent of selected TCNF/ALG precursors were measured to find the optimum formulations for 3D bioprinting. hMFCs were mixed with TCNF/ALG precursors with suitable formulations and 3D bioprinted into cylindrical disc constructs and crosslinked with CaCl2 after printing. The bioprinted constructs then underwent 6 weeks of in vitro chondrogenesis in hypoxia prior to analysis with biomechanical, biochemical, molecular, and histological assays. hMFCs mixed with a collagen I gel were used as a control. Results: The TCNF/ALG and collagen-based constructs had similar compression moduli. The expression of COL2A1 was significantly higher in TCNF/ALG. The TCNF/ALG constructs showed more of an inner meniscus-like phenotype while the collagen I-based construct was consistent with a more outer meniscus-like phenotype. The expression of COL10A1 and MMP13 were lower in the TCNF/ALG constructs. In addition, the immunofluorescence of human type I and II collagens were evident in the TCNF/ALG, while the bovine type I collagen constructs lacked type II collagen deposition but did contain newly synthesized human type I collagen.